The Historically Entangled Performer - Beghin, Tom (Leuven, Belgium LUCA School of Arts, 2023)
Keynote Lecture
To be an “historically informed performer” first and foremost means to be a “thing-entangled performer.” Following a concept of “entanglement,” as developed by the archaeologist Ian Hodder (2012/2023), this talk argues that more than focusing on traditionally “musical” matters as we read our scores, it is the historical material environment that we should inhabit and embody. Materiality is here defined more broadly than just instruments—e.g., also the hearing machine that the deaf Beethoven had constructed for his Broadwood piano. Within those instruments, it also includes an awareness of specific components or characteristics—such as the keys of Beethoven’s French Erard piano, which had a different shape than those of the Viennnese pianos he was familiar with.
FRIS
0
Keywords: Declassifying the Classics: Rhetoric, Technology, and Performance, 1750-1850